Long-term outcomes following drug-coated balloons versus thin-strut drug-eluting stents for treatment of in-stent restenosis in Chronic Kidney Disease (CKD Dragon-Registry) - Rafał Januszek; Marta Chamera; Sylwia Iwańczyk; Fabrizio D’Ascenzo; Łukasz Kuźma; Brunon Tomasiewicz; Piotr Niezgoda; Rafał Wolny; Mariusz Kowalewski; Maciej Wybraniec; Krzysztof Reczuch; Sławomir Dobrzycki; et al. (PLoS ONE, 2025)
We sought to investigated the outcomes of patients with chronic kidney disease (CKD) and drug-eluting stent (DES)-in-stent restenosis (ISR) undergoing percutaneous coronary intervention (PCI) with a drug-coated balloon (DCB) or thin strut drug-eluting stent (thin-DES). Consecutive patients with DES-ISR who underwent PCI with a thin-DES or a paclitaxel-coated DCB for DES-ISR were enrolled. The primary outcome was target lesion revascularization (TLR), while the secondary was target vessel revascularization (TVR) and device-oriented composite endpoint (DOCE). The pooled analysis included 1,317 patients, with 585 (44.42%) treated using a thin-DES and 732 (55.58%) by DCB. In the crude analysis of CKD patients (n = 286) undergoing PCI for ISR, thin-DES vs. DCB showed similar outcomes for TLR (hazard ratio [HR]=0.94, 95% confidence interval [CI]=0.44–2.00; p = 0.873), TVR (HR = 0.82, 95% CI = 0.44–1.55; p = 0.542), MI (HR = 0.71, 95% CI = 0.34–1.46; p = 0.348) and DOCE (HR = 0.71, 95% CI = 0.36–1.40; p = 0.325). After propensity score matching (n = 184), the HRs remained non-significant for TLR (0.52, 95% CI = 0.21–1.29; p = 0.159), TVR (0.54, 95% CI = 0.24–1.01; p = 0.134), MI (0.56, 95% CI = 0.24–1.32; p = 0.183), TV-MI (0.56, 95% CI = 0.09–3.39; p = 0.528), cardiac death (0.63, 95% CI = 0.10–3.81; p = 0.615), and DOCE (0.45, 95% CI = 0.19–1.04; p = 0.062). In conclusion, in CKD patients undergoing PCI for ISR, thin‐DES treatment was associated with a numerical reduction in TLR, TVR, and DOCE compared with DCB. However, these differences did not achieve statistical significance in the crude or propensity score-matched analyses.